I Know Some People: The Association of Social Capital With Primary Health Care Utilization of Residents in China - Zhang, Weiwei; Huang, Yuankai; Lu, Mengqing; Lin, Guohua; Wo, Tian; Xi, Xiaoyu (Frontiers in Public Health, 2021)
Background: Primary health-care services are underused due to the unbalanced distribution of medical resources. This is especially true in developing countries where the construction of primary health care systems has begun to take effect. And social capital is one of the important factors affecting primary health care utilization. Method: This study investigated the utilization of primary health care services by Chinese community residents in the past year. Social capital, primary health care utilization, age, healthcare insurance, etc. were measured. A multilevel negative binomial model was adopted to analyse the association of social capital with primary health care utilization. Results: data of 5471 residents from 283 communities in China were collected through a questionnaire survey in 2018. The results showed that community social capital is significantly associated with primary health care utilization in China, but individual social capital had no significant association with primary health care utilization. A one-standard-deviation increase in the community social capital leads to a 1.9% increase in primary health care utilization. Other factors like gender, education, income, health insurance, health status, etc. are significantly associated with primary health care utilization in China. Conclusions: Community social capital plays a more important role in promoting primary health care utilization, while individual social capital takes an unclear place in primary health care utilization by the residents in China.